The association of simple renal cysts with abdominal aortic aneurysms and their impact on renal function after endovascular aneurysm repair. (April 2016) - Spanos, Konstantinos; Rountas, Christos; Saleptsis, Vasileios; Athanasoulas, Athanasios; Fezoulidis, Ioannis; Giannoukas, Athanasios D
We validated the association of simple renal cysts with abdominal aortic aneurysm and other cardiovascular factors and assessed simple renal cysts' impact on renal function before and after endovascular abdominal aortic aneurysm repair. A retrospective analysis of prospectively collected data was conducted. Computed tomography angiograms of 100 consecutive male patients with abdominal aortic aneurysm who underwent endovascular abdominal aortic aneurysm repair (Group 1) were reviewed and compared with 100 computed tomography angiogram of aged-matched male patients without abdominal aortic aneurysm (Group 2). Patients' demographic data, risk factors, abdominal aortic aneurysm diameter, the presence of simple renal cyst and laboratory tests were recorded. No difference was observed between the two groups in respect to other cardiovascular risk factors except hyperlipidemia with higher prevalence in Group 1 ( p  < 0.05). Presence of simple renal cysts was independently associated with age ( p  < 0.05) and abdominal aortic aneurysm ( p  = 0.0157). There was no correlation between simple renal cysts and abdominal aortic aneurysm size or pre-operative creatinine and urea levels. No difference was observed in post-operative creatinine and urea levels either immediately after endovascular abdominal aortic aneurysm repair or in 12-month follow-up. In male patients, the presence of simple renal cysts is associated with abdominal aortic aneurysm and is increasing with age. However, their presence is neither associated with impaired renal function pre-endovascular abdominal aortic aneurysm repair and post-endovascular abdominal aortic aneurysm repair nor after 12-month follow-up.